Analysis of the Percentage of Corn Cob Bioethanol Volume with 92 Octane Fuel in Gasoline Engines - Yuniarto Agus Winoko; Supa Kusuma Aji; Agus Setiawan; Intan Fadillah (Widyagama University of Malang, 2024)
One way to improve the performance of gasoline engines is by using bioethanol, which can enhance combustion efficiency. Bioethanol, a renewable fuel derived from the fermentation of plant materials, can be blended with traditional fossil fuels to create a more efficient and environmentally friendly fuel alternative. The combination of fossil fuel and fermentation-derived fuel has a significant impact on the overall performance and emissions of the engine. The aim of this study is to determine the magnitude of changes in torque and power when a gasoline engine is fueled with a mixture of corn cob bioethanol and pertamax. Additionally, specific fuel consumption will be determined to evaluate the fuel efficiency. The engine used in this study is a 150cc gasoline motor, a common size for motorcycles and small vehicles. The testing variables include engine speed variations from 2000 to 9500 rpm using bioethanol blends of 5%, 10%, and 15% with 92 octane fuel. The data collected from these tests is calculated mathematically. The results of the study show the largest increase in power at 0.45 horsepower at 2500 rpm and torque at 2.82 Nm at 2500 rpm when using the BE15% fuel blend, indicating a notable enhancement in engine performance with higher bioethanol content. Furthermore, the smallest decrease in fuel consumption was recorded at 0.1739 kg per horsepower, highlighting the efficiency benefits of bioethanol blends. Overall, the engine performance improves when using a blend of 92 octane fuel with bioethanol compared to pure 92 octane fuel. This suggests that incorporating bioethanol into gasoline can not only improve power and torque but also enhance fuel efficiency, making it a viable option for reducing dependency on fossil fuels and lowering emissions.